SWOT Analysis of LAZISMU in Poverty Alleviation from an Islamic Economic Perspective - Maya Nur Cholida; Rani Dewi Rahmawati; Silvia Maura Madrim; Budi Jaya Putra (Universitas Darussalam Gontor, 2024)
LAZISMU (Lembaga Amil Zakat, Infaq, and Shadaqah Muhammadiyah) has shown significant performance in poverty alleviation in Indonesia from an Islamic economic perspective. Through transparent and accountable management of zakat, infaq, and shadaqah, LAZISMU is able to distribute targeted assistance to people in need. This research analyzes the performance of LAZISMU (Lembaga Amil Zakat, Infaq, dan Shadaqah Muhammadiyah) in poverty alleviation from an Islamic economic perspective using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). This method helps identify the strengths, weaknesses, opportunities, and threats faced by LAZISMU in the implementation of its social programs. The results of the analysis show that LAZISMU has strengths in its extensive network and support from the community as well as Muhammadiyah organizations, which gives it legitimacy and high trust. However, weaknesses such as limited human resources and non-optimal management are still a challenge. Great opportunities lie in the increasing public awareness of the importance of zakat and infaq, as well as government support in the economic empowerment of the people. Threats faced include competition with other amil zakat institutions and changes in government policies that may affect LAZISMU's operations. With the right approach and grounded in Islamic economic principles, LAZISMU has great potential to contribute significantly to poverty alleviation in Indonesia